(untitled) (Eurasian Journal of Engineering and Technology, 2024)
This article explores advanced methods for calculating stabilized states in open distribution electrical networks operating within the voltage range of 35-110 kV. The stability of such networks is crucial for ensuring the reliable and efficient supply of electrical power. The study focuses on a comprehensive literature analysis, highlighting existing challenges and gaps in current methodologies. Various methods for calculating stabilized states are discussed in detail, followed by the presentation of results obtained through these techniques. The article concludes with a discussion of the findings, drawing meaningful insights, and suggesting recommendations for enhancing the stability assessment of open distribution electrical networks